COGNITIVE INQUIRY: IS ENGLISH REALLY DIFFICULT FOR SCIENCE STUDENTS? - Rosdiana; Nyak Mutia Ismail (English Education Department, 2017)
Science students are known miserable in coping very well with language, especially English. This study searched for the truth of this proposition by evaluating the formative test items for senior high-school level used in a science-based school in Aceh, Indonesia. The sources of this study were 150 questions and 35 students’ answers on the pertaining tests for three different grades. The objective of this study was to find out the item facility and distractors’ efficiency of each test item used for science students in their formative test. Methodology deployed was qualitative approach using content analysis in the scope of finding the item facility and distractors’ efficiency for the test items. The result depicted that 84% of the items are in the ‘easy’ index, and 11% in ‘moderate’ index, and 4% ‘difficult’ index. Then, the data show that only 17% of the distractors’ are efficient. The conclusion is that the formative test items are, indeed, easy for science students but with one condition: most of the distractors do not work properly for their cognitive level.